Activity of Sedimentary Fly Ash Aerated Concrete. Issue 4 (11th October 2018) - Chen, Yan-Fei; Yang, Dong-Sheng; Xie, Li-Lan; Yang, Xiao-Song; Wu, Yi-Ru; Huang, Yan-Jia
Abstract : The key technology for the production of aerated concrete, by using sedimentary fly ash to replace the new fly ash, is of enormous interest to the concrete industry. The chemical composition, mineral composition and microstructure of the sedimentary fly ash in Qian-Xi Power Plant (QXPP), Gui-Yang Power Plant (GYPP) and Qing-Zhen Power Plant (QZPP) are presented. The activity of the sedimentary fly ash aerated concrete is tested in detail by employing grinding, mineral admixtures and chemical admixtures. The results show that the sedimentary fly ash is essentially low calcium fly ash. The mineral composition of the sedimentary fly ash is basically the same as that of the new fly ash. The compressive strength and flexural strength of the grinded fly ash specimens are larger than that of untreated fly ash. The mineral admixture SH1 and SH2 for sedimentary fly ash aerated concrete can increase the compressive and flexural strength. The excitation effect of SIII-activator, SIV-activator and SV-activator are better than other activators. The best chemical admixture is CaO-SIV-activator. These studies are of significance for the use of sedimentary fly ash in aerated concrete. This study provides a new way to eliminate the sedimentary fly ash.